2018
DOI: 10.1080/08959420.2018.1500857
|View full text |Cite
|
Sign up to set email alerts
|

Working Hours Flexibility and Timing of Retirement: Findings from Europe

Abstract: This study investigates how flexibility in working hours affects retirement timing. It tests the assumption that decreasing weekly working hours delays retirement and extends working life. Using data from four waves of the Survey of Health, Ageing and Retirement in Europe (SHARE) and of the English Longitudinal Study of Ageing (ELSA), we analyze whether a shift from full-time to part-time work delays retirement. Results show that older workers who reduce their working hours retire earlier than those who stay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Wainwright et al 2019 ). However, there is a risk of part-time work becoming a stepping stone into full retirement instead of leading to an extended working life (Hess et al 2018 ). The causal mechanisms of part-time work, informal help and formal volunteering in late careers, and their implications for the timing of labour market exit, are issues to be further explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Wainwright et al 2019 ). However, there is a risk of part-time work becoming a stepping stone into full retirement instead of leading to an extended working life (Hess et al 2018 ). The causal mechanisms of part-time work, informal help and formal volunteering in late careers, and their implications for the timing of labour market exit, are issues to be further explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with an earlier study based on nine OECD countries with FRPs that found a widespread and sudden decline in labor force participation at and even before the statutory retirement age (Börsch-Supan et al, 2017). Similarly, a study of 14 European countries showed that policies allowing part-time work at the end of an occupational career did not encourage the prolongation of working life (Hess, Bauknecht, & Pink, 2018). Thus, the trend of moving away from early retirement schemes toward flexible retirement schemes does not necessarily lead individuals to retire later.…”
Section: Discussionmentioning
confidence: 99%
“…Working‐hour characteristics may also change according to seniority and possibilities to select more favourable working hours (Hess, Bauknecht, & Pink, 2018; Vanajan, Bultmann, & Henkens, 2019). This could explain some earlier negative results on age‐related trends in the association of shift work and health (Booker, Magee, Rajaratnam, Sletten, & Howard, 2018; Ritonja, Aronson, Matthews, Boivin, & Kantermann, 2019).…”
Section: Introductionmentioning
confidence: 99%